Efficiency of maize cultivars in the absorption and use of nitrogen in a greenhouse environment - Carvalho, Rafael Pelloso de; Von Pinho, Renzo Garcia; Davide, Livia Maria Chamma (Semina: Ciências Agrárias, 2012)
The objectives of this study were to evaluate corn cultivars for efficiency in the absorption and use of nitrogen (N) levels of efficiency through the use of nitrogen in contrasting levels of this nutrient in the greenhouse. The experiment was carried out in a greenhouse and the experimental design was in randomized blocks, with 20 treatments and four replicates, in a 10 x 2 factorial arrangement. All 10 maize cultivars were represented by local varieties and commercial hybrids, and the applied N levels were 100 and 400 mg dm-3. Plots were represented by 8L pots containing 4 plants each, which were harvested in phenological stage V8. The evaluated characteristics were dry matter weight and N level of shoot and roots. The nutritional efficiency of cultivars was also evaluated. The studied cultivars had distinct characteristics concerning N use and absorption efficiency in environments of high and low nitrogen levels. The contrasting N levels allowed the occurrence of differences needed to distinguish the most efficient cultivars. Genotypes efficient for N use and responsive to its application can be selected based on the indexes used in this work.